The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.18311/jnr/2016/654
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Ethanolic Extract of <i>Borassus flabellifer Flowers for its Antidiabetic and Antioxidant Potential

Abstract: Ipomoea reniformis Chaos is claimed in Indian traditional medical practice to be useful in the treatment of epilepsy and neurological disorders. In the present study, pretreatment effect of methanolic extract of Ipomoea reniformis on epilepsy and psychosis was evaluated in rodents using standard procedures. Besides evaluating epileptic and behavioral parameters, neurotransmitters such as Gamma-Amino Butyric Acid (GABA) in epilepsy and in psychosis dopamine, noradrenaline and serotonin contents in the rodent br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, part of B. flabellifer contained different amounts of total flavonoids. The total flavonoid content in quercetin equivalent in B. flabellifer flower was significantly higher than the root [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, part of B. flabellifer contained different amounts of total flavonoids. The total flavonoid content in quercetin equivalent in B. flabellifer flower was significantly higher than the root [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tusskorn et al showed that the male flower of B. flabellifer extracted by ethyl acetate and chloroform had the IC 50 values of 287.03 ± 6.90 and >1000 µg/mL, respectively [ 16 ]. Kavatagimath et al reported that the B. flabellifer male flower extracted by 95% ethanol and butylated hydroxytoluene had the IC 50 values of 460 and 419 µg/mL, respectively [ 18 ]. The IC 50 values of B. flabellifer male flower ethanolic extract reported in our study showed a significantly lower value indicating that the male flower ethanolic extract had a superior antioxidant activity compared with the other solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal fruits stand a great chance in controlling blood sugar levels and exerting antidiabetic activity due to the pharmacologically active phytoconstituents present in them [29] . While looking for natural options, researchers stumbled upon the ethanolic extract of B. flabellifer flowers and observed a decrease in the blood glucose levels when administered to alloxan induced diabetic rats [30] .…”
Section: Resultsmentioning
confidence: 99%
“…6 Previous studies have reported the presence of phytochemical compounds and their corresponding bioactivities in various organs of B. flabellifer L. For instance, the root contains alkaloids, flavonoids, and tannins with antimicrobial, antioxidant, and anti-inflammatory activities, 7 while the flowers contain flavonoids, saponins, tannins, and phenolics with antioxidant and anti-inflammatory activities. 8,9 However, it is difficult to find studies on other specific compounds in this plant. Therefore, an attempt to screen the phytochemicals in this plant using the High-Performance Liquid Chromatography (HPLC) method was conducted.…”
Section: Introductionmentioning
confidence: 99%